The Influence of Transformational Leadership and Organizational Culture on Private University Lecturers’ Performance in Bandar Lampung - Khairul Saleh; Nuzleha; Ani Pujiati (Lembaga Publikasi Ilmiah Nusantara, 2026)
This research examines the influence of transformational leadership and organizational culture on lecturers' performance, with organizational commitment as a mediating variable, in private universities in Bandar Lampung. The study employed a quantitative research design and analyzed the data using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The population consisted of permanent lecturers registered in PDDikti at private higher education institutions in Bandar Lampung. A total of 200 valid respondents were selected through purposive sampling. Data were gathered using questionnaires based on a five-point Likert scale. The findings show that transformational leadership has a positive and significant influence on organizational commitment (β = 0.412; p < 0.05) and lecturer performance (β = 0.356; p < 0.05). Organizational culture also has a positive and significant effect on organizational commitment (β = 0.378; p < 0.05) and lecturer performance (β = 0.329; p < 0.05). In addition, organizational commitment has a positive and significant effect on lecturer performance (β = 0.445; p < 0.05). The results further indicate that organizational commitment partially mediates the relationships between transformational leadership and lecturer performance, and between organizational culture and lecturer performance. From a practical perspective, these findings suggest that leaders of private universities need to focus on developing transformational leadership, strengthening an academic culture that supports performance, and enhancing lecturer commitment. These aspects can serve as strategic efforts to improve teaching productivity, research performance, community service activities, and the overall competitiveness of higher education institutions.